Predation of Five Generalist Predators on Brown Planthopper (Nilaparvata lugens Stål) - Sri Karindah (Perhimpunan Entomologi Indonesia, 2011)
Two generalist predators of brown planthopper,Metioche vittaticollis and Anaxipha longipennis (Gryllidae) have not been much studied in Indonesia. This research was conducted to study and compare the predatory ability of M. vittaticollis, A. longipennis (Gryllidae) and three coleopterans, Paederus fuscipes (Staphylinidae), Ophionea sp. (Carabidae),and Micraspis sp. (Coccinellidae) against brown planthopper (fourth and fifth instars) under laboratory condition. In total, 20 nymphs of N. lugens were exposed for 2 hour to each predator for 5 consecutive days. Prey consumptions by the predatory crickets, M. vittaticollis and A. longipennis were greater than the other predators and followed by A. longipennis, Micraspis sp., P. fuscipes, and Ophionea sp. respectively. Consumption rates of M. vittaticolis and A. longipenis were also higher than other predators. Micraspis sp was more active on predation in the morning,while M. vittaticollis, A. longipennis, P. fuscipes, and Ophionea sp. were more active both in the morning and the night but not in the afternoon. However, all five species of predators were not so active in preying during the afternoon. In conclusion, a major effort should be extended to conserve these predatory crickets especially M. vittaticollis and A. longipennis.